Preoperative Imaging Modalities to Predict the Risk of Regional Nodal Recurrence in Well-Differentiated Thyroid Cancers - AlNoury, Mohammed K.; Almuhayawi, Saad M.; Alghamdi, Khalid B.; Al-Noury, Khaled I. (International Archives of Otorhinolaryngology, 2015)
Introduction Thyroid cancer incidence has increased in the previous 2 decades. Preoperative identification of lymph node metastasis is a suggested risk factor associated with recurrence following thyroidectomy.Objectives We aimed to evaluate the accuracy of preoperative radiologic investigations of nodal status in determining the postoperative risk of regional nodal recurrence in cases of well-differentiated thyroid cancer.Methods This is a case series. We retrospectively reviewed data, including preoperative ultrasonography and/or computed tomography results, on patients who underwent total thyroidectomy for thyroid cancer at our hospital between 2006 and 2012. Prognostic factors for predicting recurrence, including age, sex, tumor diameter, and nodal diameter, were evaluated.Results Total thyroidectomy was performed on 24 male and 74 female patients (median age, 43 years). The median follow-up time was 21 months. Sixty-eight patients had papillary thyroid cancer, and 30 had follicular cancer. Nodal recurrence was evident in 30% of patients, and 4% of patients died. Identification of lymph node involvement during preoperative radiologic investigations was strongly prognostic for recurrence: 35.3% of patients with positive preoperative ultrasonography findings and 62.5% of those with positive preoperative computed tomography findings had recurrence (p = 0.01).Conclusions Preoperative identification of lymph node metastasis on radiologic studies was correlated with an increased risk of regional nodal recurrence in well-differentiated thyroid cancer. Computed tomography was superior to ultrasonography in detecting metastatic nodal involvement preoperatively and is therefore recommended for preoperative assessment and postoperative follow-up.
Keywords: thyroid neoplasms; recurrence; ultrasonography; computed tomography; X-ray